2001
DOI: 10.1021/ie0009637
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of CH3SH in a RF Plasma Reactor:  Reaction Products and Mechanisms

Abstract: Application of the RF (radio frequency) cold plasma method to the decomposition of methanethiol (methyl mercaptan, CH 3 SH) at different O 2 /CH 3 SH ratios (0-4.5), with various input powers (20-90 W), and at constant operating pressure (30 Torr) was investigated. The species detected in the CH 3 SH/O 2 /Ar RF plasma were SO 2 , CS 2 , OCS, CO, CO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 58 publications
1
49
0
Order By: Relevance
“…In previous studies, rf plasma has been successfully applied to destroy hazardous air pollutants, such as chloromethane (CH 3 Cl), trifluoromethane (HFC-23, or CHF 3 ), ethylene oxide, and CH 3 SH. [11][12][13][14] Other plasma alternatives developed for the destruction of H 2 S, SO 2 , and ammonia (NH 3 ) at atmospheric pressure were usually only suitable to low concentrations of odorant (on the order of approximately several hundred ppmv). [15][16][17] Previous conversion processes showed that the gaseous oxidation of DMS at 473 K yielded SO 2 and aldehydes as the primary products; the gas-phase pyrolysis of DMS generated the major products methane (CH 4 ), ethylene (C 2 H 4 ), H 2 S, and CS 2 , with small amounts of C 2 H 5 SH and yellowish compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, rf plasma has been successfully applied to destroy hazardous air pollutants, such as chloromethane (CH 3 Cl), trifluoromethane (HFC-23, or CHF 3 ), ethylene oxide, and CH 3 SH. [11][12][13][14] Other plasma alternatives developed for the destruction of H 2 S, SO 2 , and ammonia (NH 3 ) at atmospheric pressure were usually only suitable to low concentrations of odorant (on the order of approximately several hundred ppmv). [15][16][17] Previous conversion processes showed that the gaseous oxidation of DMS at 473 K yielded SO 2 and aldehydes as the primary products; the gas-phase pyrolysis of DMS generated the major products methane (CH 4 ), ethylene (C 2 H 4 ), H 2 S, and CS 2 , with small amounts of C 2 H 5 SH and yellowish compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The mole fraction of the product species was determined by comparing with the response of the peak height of standard gas at the same wavenumber. 13,14 However, the concentrations of SF 4 and S 2 F 10 were estimated from data of Heise et al 15 and Wilmshurst and Bernstern. 16 All unreacted F atoms were assumed to be converted into F 2 , 17 and the mole fraction of F 2 was determined using a mass balance.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Decomposition of CH 3 SH in a RF Plasma Reactor: Reaction Products and Mechanisms Tsai et al (2001) studied the application of the RF cold plasma method to the decomposition of methanethiol (methyl mercaptan, CH 3 SH) at different O2/CH3SH ratios (0−4.5), with various input powers (20−90 W), and at constant operating pressure (30 Torr). The species detected in the CH 3 SH/O 2/ Ar RF plasma were SO 2 , CS 2, OCS, CO, CO 2, CH 4 , C 2 H 4 , C 2 H2, H 2 , H 2 O, HCOH, and CH 3 OH.…”
Section: (4) Decomposition Of Boron Trifluoride In the Rf Plasma Envimentioning
confidence: 99%
“…An advantage of using the RF plasma reactor is that a conventional reaction therein can be completed at a lower temperature elsewhere (Hsieh et al, 1998a). Many studies have demonstrated that the destruction or treatment of hazardous gases by applying RF plasma technology is very practical Li et al, 1996;Hsieh et al, 1998a, b, c;Wang et al, 1999a, b;Liao et al, 2000;Wang et al, 2000;Hsieh et al, 2001;Liao et al, 2001;Tsai et al, 2001;Shih et al, 2002;Tsai et al, 2002;Shih et al, 2003;Tsai et al, 2003;Wang et al, 2003;Tsai et al, 2004;Liao et al,2005;Wang et al, 2005a, b;Hsieh et al, 2007;Tsai et al, 2007). The above mentioned cited articles (from 1996 to 2007) show that RF power is delivered through the power meter and the matching unit to an outer copper electrode that is wrapped around the reactor, the other electrode is earthed.…”
Section: Introduction and A Brief Review Of Decomposition Of Air Toximentioning
confidence: 99%